2020
DOI: 10.3390/met10101357
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role and Mechanism of Nano MgO on the Hot Compressive Deformation Behavior of Mg-Zn-Ca Alloys

Abstract: Aiming to investigate the role and mechanism of nano MgO on the hot compressive deformation behavior of Mg alloys, the Mg-3Zn-0.2Ca alloy (MZC, in wt%) and the 0.2MgO/Mg-3Zn-0.2Ca alloy (MZCM, in wt%) were investigated systematically in the temperature range of 523–673 K and the strain rate range of 0.001–1 s−1. MZCM shows finer grains and second phase because of the refinement effects of added MgO. Flow behavior analysis shows that the addition of nano MgO promotes the dynamic recrystallization (DRX) of MZC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In accordance with Equations ( 5) and ( 6 Because there are three variations in Equation ( 4), by calculating partial differential for temperature and strain rate, respectively, the linear relationship of ln[sinh(ασ)] − 1000 ε − ln[sinh(ασ)] is 3.68. Accordingly, the current activation energy, Q, is estimated to be 186.3 kJ/mol, which is higher than that of the self-diffusion in pure Mg. Zheng et al [29] researched the effect of the addition of MgO on the plastic deformation behavior of Mg alloy and indicated that the lower activation energy (150.3 kJ/mol) can be attribute to the fine grains and second phases. In this study, the moderate Q value can be attributed to the exceptional fine grain size and the occurrence of numerous second phases, such as Mg 2 Ca and Mg-Zn-Ce phases (T' phase).…”
Section: Constitutive Analysis Based On Arrhenius Equationmentioning
confidence: 99%
“…In accordance with Equations ( 5) and ( 6 Because there are three variations in Equation ( 4), by calculating partial differential for temperature and strain rate, respectively, the linear relationship of ln[sinh(ασ)] − 1000 ε − ln[sinh(ασ)] is 3.68. Accordingly, the current activation energy, Q, is estimated to be 186.3 kJ/mol, which is higher than that of the self-diffusion in pure Mg. Zheng et al [29] researched the effect of the addition of MgO on the plastic deformation behavior of Mg alloy and indicated that the lower activation energy (150.3 kJ/mol) can be attribute to the fine grains and second phases. In this study, the moderate Q value can be attributed to the exceptional fine grain size and the occurrence of numerous second phases, such as Mg 2 Ca and Mg-Zn-Ce phases (T' phase).…”
Section: Constitutive Analysis Based On Arrhenius Equationmentioning
confidence: 99%
“…The microstructure of Mg-Ca alloys systems includes α-Mg (hexagonal crystalline structure) and Mg 2 Ca phase, in which crystalline cell presents double parameter values (a = 0.623, c = 0.1012) compared to those of Mg [55][56][57][58]. The standard electrode potential of Ca is more negative (−2.87 V SHE ) than that of Mg and it may be assumed that Ca 2+ will be released, originating from the Mg 2 Ca particles, considered as an anodic active [54,[59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%